Fast modulations of pulsating proton aurora related to subpacket structures of Pc1 geomagnetic pulsations at subauroral latitudes. Issue 15 (14th August 2016) - Ozaki, M.; Shiokawa, K.; Miyoshi, Y.; Kataoka, R.; Yagitani, S.; Inoue, T.; Ebihara, Y.; Jun, C.‐W; Nomura, R.; Sakaguchi, K.; Otsuka, Y.; Shoji, M.; et al.
Abstract: To understand the role of electromagnetic ion cyclotron (EMIC) waves in determining the temporal features of pulsating proton aurora (PPA) via wave‐particle interactions at subauroral latitudes, high‐time‐resolution (1/8 s) images of proton‐induced N2 + emissions were recorded using a new electron multiplying charge‐coupled device camera, along with related Pc1 pulsations on the ground. The observed Pc1 pulsations consisted of successive rising‐tone elements with a spacing for each element of 100 s and subpacket structures, which manifest as amplitude modulations with a period of a few tens of seconds. In accordance with the temporal features of the Pc1 pulsations, the auroral intensity showed a similar repetition period of 100 s and an unpredicted fast modulation of a few tens of seconds. These results indicate that PPA is generated by pitch angle scattering, nonlinearly interacting with Pc1/EMIC waves at the magnetic equator. Key Points: Fast (a few tens of seconds) modulation of pulsating proton aurora was observed Fast modulations of pulsating proton aurora were related with subpacket structures of Pc1 pulsations The modulation frequency showed a correlation with Pc1 intensity based on a nonlinear theory